(untitled) (Journal of the College of Basic Education, 2022)
An experiment was conducted during the winter season 2013 in the Botanical Garden of the Department of Life Sciences in the College of Education for Pure Sciences (Ibn Al-Haytham) / University of Baghdad, with the aim of studying the effect of vitamin C at concentrations 40 and 80 ppm and aspirin (salicylic acid) at concentrations 50 and 100 ppm in Growth of the chard plant Beta vulgaris L..The results showed an increase in plant height, number of leaves, leaf length and width, leaf area, leaf weight ratio, fresh and dry weights, nitrogen, phosphorus, potassium and iron content in the leaves of chard compared to control plants.